IMPLEMENTASI PEMBELAJARAN BAHASA ARAB DENGAN METODE QIRO’AH DIKELAS VIII M MTS ASSUNNIYYAH KENCONG-JEMBER - Zainuri, Zainuri (INCARE, International Journal of Educational Resources, 2022)
Each method has the same overall goal, so that Arabic learners can correctly master the learning material. This study uses a qualitative approach, where this research is delivered from the results of research written descriptively while the data collection technique is carried out by emphasizing the study of texts and aspects of analysis, then collecting some texts related to the material being studied by searching for related literatures, either from research material, books, journals and other articles related to the material.The results of this study indicate that the application of the qiro'ah method in learning Arabic for the students of MTs Assunniyyah Kencong-Jember needs to be combined with other methods, such as the grammatical translation method, the audio lingual method or the direct method. And as for the efforts made by the teacher in improving students' Arabic learning by providing additional learning, giving special attention and the need for emphasis on students in memorizing vocabulary.